The Methodology of Intercultural Competence Development on the Basis of a Cognitive Style-inclusive Approach; Procedia - Social and Behavioral Sciences; Vol. 154: Proceedings of The XXV Annual International Academic Conference, Language and Culture, 20-22 October 2014 - Soboleva A. V. Aleksandra Vladimirovna (2014, 2014)
Title screen